2015
DOI: 10.4172/2155-6148.1000547
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium: Emerging Potentials in Anesthesia Practice

Abstract: Magnesium, a non-competitive blocker of N-methyl-D-aspartate receptor, initially used for management of preeclampsia, arrhythmia and bronchial asthma, is of great importance in anesthesia practice nowadays. It is being used intravenously, intrathecally as well as epidurally for postoperative pain relief. Recently it has gained popularity as an adjuvant in blocks. Anesthetic and analgesic sparing characteristics of magnesium enable anesthesiologists to reduce the dose of anesthetics during surgery and the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
1
4
0
2
Order By: Relevance
“…The 21.6% difference in the MS dose administered in the groups did not result signi cant difference in the resulting magnesium blood concentrations. These concentrations were always within the safe values for patients in the study 31 .…”
Section: Discussionsupporting
confidence: 54%
“…The 21.6% difference in the MS dose administered in the groups did not result signi cant difference in the resulting magnesium blood concentrations. These concentrations were always within the safe values for patients in the study 31 .…”
Section: Discussionsupporting
confidence: 54%
“…Tese concentrations were similar to the blood magnesium concentrations in the NOG (10 patients). Tese concentrations were always within the safe values for study patients [25], as reported by Taheri et al [10]. Although they did not analyze the analgesic properties, Brookfeld et al [26] found that obese pregnant women needed a longer time to reach a therapeutic concentration of magnesium in the blood for seizure prophylaxis in preeclampsia, which was higher than the average concentration in the present trial and may be higher than the level needed to achieve postsurgical analgesia, which was higher than the average concentration in the present trial.…”
Section: Discussionmentioning
confidence: 82%
“…Segundo Coderre (1993) o magnésio bloqueia as correntes induzidas por NMDA de maneira dependente de voltagem, bloqueando os efeitos do canal receptor. Bansal (2015) ressaltou que a faixa normal de magnésio no plasma é 1,4-2,2 meq/l. A hipomagnesimia pode ocorrer com frequência após cirurgias como cirurgia abdominal, ortopédica e cardíaca, bem como após pequenas cirurgias.…”
Section: Discussionunclassified